1969
DOI: 10.1111/j.1365-2621.1969.tb00919.x
|View full text |Cite
|
Sign up to set email alerts
|

Tannins of Grain Sorghum: Luteoforol (Leucoluteolinidin), 3′,4,4′,5,7‐Pentahydroxyflavan

Abstract: General procedureGrain samples (0.5 g) were shaken gently with 50 ml of the acid reagent in 250 ml stoppered, round-bottomed flasks at specified temperatures for periods of l-3 days. Absorption curves of the colored extracts were recorded

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1975
1975
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…5,6 These are also difficult compounds to identify, largely owing to their unextractable nature. 7,8 Together with anthocyanins, PA and PB are responsible for most of the pigmentation found in mature seed coats. 2,9 Lignin, another major polymer found in seed coats, has also been associated with the fibre fraction.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 These are also difficult compounds to identify, largely owing to their unextractable nature. 7,8 Together with anthocyanins, PA and PB are responsible for most of the pigmentation found in mature seed coats. 2,9 Lignin, another major polymer found in seed coats, has also been associated with the fibre fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Becker (5) found that, among various grains, sorghum had the highest percentage of phosphorus present as part of phytic acid (75%). High tannin content in some varieties of sorghum make it difficult to digest (9,13,14,29,46; D. D. McGinty, Ph.D. thesis, Texas A&M University, College Station, Tex., 1968), and the astringency of the milled product may make it unpalatable (4,8). However, from an economic standpoint, high tannin content in sorghum may be an advantage because it renders the grain resistant to birds (51) and molds (30).…”
mentioning
confidence: 99%
“…2). Luteoforol has been prepared in the laboratory by the reduction of eriodictyol with sodium borohydride (Bate-Smith and Rasper, 1969). It is proposed that such a reduction can take place biochemically in the plant, and that, in the material studied, this reaction was under the control of gene R. In Abu Taiman, because gene T was in the recessive condition, the biosynthesis of luteoforol was blocked, and eriodictyol and its chalcone accumulated.…”
Section: Resultsmentioning
confidence: 99%